The differences of orthostatic hypotension in patients with Parkinson's disease and multiple system atrophy - Zeng, Jingrong; Xing, Yingqi; Mei, Shanshan; Xu, Baolei; Xue, Xiaofan; Song, Haixia; Xu, Erhe (Frontiers in Neurology, 2023)
Background Multiple system atrophy (MSA) and Parkinson's disease (PD) have similar clinical presentations in their early stages. Orthostatic hypotension (OH) is a common autonomic dysfunction associated with MSA and PD. Heart rate (HR) and systolic blood pressure (SBP) changes are measured in response to the active standing test, which is widely used to screen for cardiovascular autonomic function. Objectives and Methods Overall, 255 patients (67 MSA, 188 PD) underwent continuous beat-to-beat non-invasive BP monitoring and active standing test. The total standing time was 10 min, and the BP differences between both groups were compared to determine whether the ΔHR/ΔSBP can differentiate both conditions. Results Classical OH(52%) and initial OH (19%) were most common in MSA and PD, respectively. MSA had a higher HR (75.0 ±9.7 vs. 71.0 ±10.7, P=0.008) than PD in the supine position. SBP (135.70 ± 15.68 mmHg vs. 127.31 ± 15.14 mmHg, P = 0.106), diastolic BP (78.45 ± 12.36 mmHg vs. 67.15 ± 13.39 mmHg, P = 0.009) and HR (73.94 ± 8.39 bpm vs. 71.08 ± 13.52 bpm, P = 0.389) at baseline were higher in MSA-classical orthostatic hypotension (COH) than in PD-COH. After adjusting for age and disease course, the ΔHR/ΔSBP-10 min significantly discriminated MSA-COH from PD-COH (P = 0.031). An ΔHR/ΔSBP-10 min of 0.517 showed a sensitivity of 67% and specificity of 84% (AUC = 0.77, 95% CI: 0.63–0.91). Conclusion The SBP, diastolic BP, and HR were higher in the supine position; however, ΔHR and ΔSBP were lower after standing in MSA patients than in PD patients. The ΔHR/ΔSBP-10 min discriminated between MSA-COH and PD-COH with quiet acceptable accuracy.